REFLEXÕES SOBRE A POLÍTICA DE EDUCAÇÃO ESPECIAL NACIONAL E NO ESTADO DO PARANÁ - Machado, Evelcy Monteiro; Vernick, Maria da Glória Lima Pereira (Nuances: estudos sobre Educação, 2013)
This is an analytical reflective study about special education policies in Brazil and the right to education. Part of the changes planned for the area since the adoption of the Federal Constitution in 1988 and influences arising from movements and international organizations. Follows with the possibilities of deploying new organization as a result of the National Special Education in the Perspective of Inclusive Education (BRAZIL, 2008a), and it ends with the positioning of the Parana government maintaining special needs schools. This bibliographic study and documentary analysis the main legal documents that guide the National Policy on Special Education in the Perspective of Inclusive Education (BRAZIL, 2008a) reveal that the configuration of national and state (Paraná) special education occurred with impasses and political clashes, influencing the changes occurring in local networks, and in Paraná the "schooling" of pupils with special educational needs is being held both in regular schools and specialized institutions, demonstrating a dual system. Special schools, as part of a social, political and economic Brazilian educational system, keeps the hegemonic relations of the ruling class and contribute to the persistence of the relationship between public and private. http://dx.doi.org/10.14572/nuances.v24i2.2479